Safety and feasibility of sublingual microcirculation assessment in the emergency department for civilian and military patients with traumatic haemorrhagic shock: a prospective cohort study. Issue 12 (21st December 2016) - Naumann, David N; Mellis, Clare; Smith, Iain M; Mamuza, Jasna; Skene, Imogen; Harris, Tim; Midwinter, Mark J; Hutchings, Sam D
Abstract : Objectives: Sublingual microcirculatory monitoring for traumatic haemorrhagic shock (THS) may predict clinical outcomes better than traditional blood pressure and cardiac output, but is not usually performed until the patient reaches the intensive care unit (ICU), missing earlier data of potential importance. This pilot study assessed for the first time the feasibility and safety of sublingual video-microscopy for THS in the emergency department (ED), and whether it yields useable data for analysis. Setting: A safety and feasibility assessment was undertaken as part of the prospective observational MICROSHOCK study; sublingual video-microscopy was performed at the UK-led Role 3 medical facility at Camp Bastion, Afghanistan, and in the ED in 3 UK Major Trauma Centres. Participants: There were 15 casualties (2 military, 13 civilian) who presented with traumatic haemorrhagic shock with a median injury severity score of 26. The median age was 41; the majority (n=12) were male. The most common injury mechanism was road traffic accident. Primary and secondary outcome measures: Safety and feasibility were the primary outcomes, as measured by lack of adverse events or clinical interruptions, and successful acquisition and storage of data. The secondary outcome was the quality of acquired video clips according to validated criteria, in order to determine whether useful data could be obtained in this emergency context. Results: Video-microscopy was successfully performed and stored for analysis for all patients, yielding 161 video clips. There were no adverse events or episodes where clinical management was affected or interrupted. There were 104 (64.6%) video clips from 14 patients of sufficient quality for analysis. Conclusions: Early sublingual microcirculatory monitoring in the ED for patients with THS is safe and feasible, even in a deployed military setting, and yields videos of satisfactory quality in a high proportion of cases. Further investigations of early microcirculatory behaviour in this context are warranted. Trial registration number: NCT02111109.